FINANCIAL DUE DILIGENCE FOR MERGER AND ACQUISITION PT XL AXIATA TBK AND SMARTFREN TELECOM - Ilhami, Muhammad Livain; Rahadi, Raden Aswin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the financial due diligence for the proposed merger between PT XL Axiata Tbk and PT Smartfren Telecom in Indonesia’s competitive telecommunications industry. This research provides a detailed analysis of financial performance, liquidity, solvency, synergy value, and valuation using Discounted Cash Flow (DCF) methodology. The findings reveal that XL Axiata demonstrates financial strength, with strong profitability and operational efficiency metrics, while Smartfren Telecom exhibits financial vulnerabilities, including liquidity and solvency challenges. The synergy value of the merger is estimated to create significant economic gains by leveraging operational efficiencies, cost reductions, and revenue expansion opportunities. The combined entity’s potential for improved competitive positioning and sustainable growth is supported by the projected creation of 8,626 billion in synergy value. However, the Altman Z-Score analysis flags financial distress for both companies, necessitating focused risk mitigation strategies and effective post-merger integration. This research underscores the merger’s potential to enhance shareholder value and market competitiveness while highlighting the critical importance of addressing integration challenges and financial risks. The study provides a framework for evaluating similar mergers within the capital-intensive telecommunications sector.